1983
DOI: 10.1128/iai.41.3.1010-1015.1983
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity but not arthritogenicity of Mycoplasma arthritidis for mice associates with the haplotype expressed at the major histocompatibility complex

Abstract: The use of inbred and congenic mouse strains established that toxicity and death induced by Mycoplasma arthritidis associates with the haplotype expressed at the murine major histocompatibility complex. Mice bearing H-2k and H-2d are susceptible, whereas those bearing H-2b are much more resistant. Mice susceptible to toxicity exhibited massive peritoneal adhesions and a decreased ability to clear organisms from the peripheral circulation. However, the severity of acute arthritis developing over a 3-month perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The crossreaction observed between anti-M. arthritidis and M. pulmonis ELISA antigens was not reduced by addition of 1% horse serum to the diluent (Table 3). Antiserum to broth- inoculated control animals has been shown previously to be unreactive in the ELISA (10).…”
mentioning
confidence: 96%
“…The crossreaction observed between anti-M. arthritidis and M. pulmonis ELISA antigens was not reduced by addition of 1% horse serum to the diluent (Table 3). Antiserum to broth- inoculated control animals has been shown previously to be unreactive in the ELISA (10).…”
mentioning
confidence: 96%
“…In experiments with inbred and congenic strains of mice, it was demonstrated that toxicity and death induced by M. arthritidis were associated with the major histocompatibility complex (MHC) haplotypes expressed. Mice possessing the H-2k or H-2d haplotype were susceptible, whereas those expressing H-2b appeared to be more resistant (10). Further influences asserted by the MHC haplotype were on an ulcerative dermal coagulation necrosis upon subcutaneous injection of M. arthritidis (7) and a reactivity of mouse lymphocytes toward M. arthritidis supernatants (MAS) acting as a soluble T-cell mitogen (5,9).…”
mentioning
confidence: 99%
“…Pyrogenic exotoxins stimulate macrophages to produce mediators such as IL-1 and TNF and production of these mediators was induced by products of mycoplasma [17][18][19]. Mycoplasmas produce haemolysins and cytotoxic substances that affect rat, mouse and chicken embryos and foetal rat skin fibroblasts [20][21][22]. These toxic materials might act on cells of the immune system to induce cytokines such as macrophage deactivating factor (MDF) or TGF-/3 resulting in suppression of macrophage antimicrobial activity that would account for the survival of mycoplasma.…”
Section: Discussionmentioning
confidence: 99%